SOLUBILITY ENHANCEMENT, FORMULATION DEVELOPMENT AND EVALUATION OF IMMEDIATE RELEASE TABLET OF ANTIHYPERTENSIVE DRUG TADALAFIL - Sisodiya, Mayuri; Saudagar, Ravindranath (Journal of Drug Delivery and Therapeutics, 2018)
The objective of the study was to enhance the solubility and dissolution rate of Tadalafil using hydrophilic carriers such as PVP K-30, Poloxamer 188, Sodium starch glycolate and compatibility study of Tadalafil with different polymers by FTIR. Characterization of solid dispersion-FTIR, DSC and phase solubility analysis was study to improve the oral bioavailability. Formulation and evaluation of immediate release tablets prepare from solubility enhanced Tadalafil. Among the various approaches Solvent evaporation has gained good acceptance in recent years in the industry for enhancing the solubility and dissolution rate of poorly soluble drugs. Poloxamer 188 used as polymer as it is good solubilizing agent. As per the phase solubility studies, a 32 factorial study were used to prepare the immediate release tablet and evaluated for the interactions and in vitro drug release. Sodium Starch Glycolate and PVP used as superdisintegrants. The solubility of tadalafil in selected ratios containing tadalafil and Poloxamer 188 solid dispersion prepared by solvent evaporation was determined. From the various ratios 1:0.5 was resulted in a much higher enhancement (9.75folds). Fourier transform infrared spectroscopy (FT-IR) and differential scanning calorimetry (DSC) studies conducted, explain overall drug and excipients compatibility. More than 90% of tadalafil was released from IR tablet within 30 min. There is enhancement of the solubility rate if tadalafil by solid dispersion with Poloxamer 188 prepared by solvent evaporation method. The compatibility studies of the drug and polymers showed that there was no incompatibility between them. Wet granulation method showed that, the desired flow properties for the compression into tablets. Tablets were prepared using wet granulation method resulted into simple, cheap, more suitable method for the manufacturing immediate release dosage form.